2001
DOI: 10.1007/s004280000373
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel density in pituitary adenomas and carcinomas

Abstract: Tumor growth depends on several factors, including angiogenesis. Tumors cannot grow if new vessels are not formed to supply the cells with oxygen and other nutrients and to remove waste products. Increased angiogenesis can be correlated with tumor growth and metastatic potential in many tumor types, indicating that neoformation of vessels is a prognostic indicator of tumor behavior. We evaluated microvessel densities in 157 various pituitary adenoma types and seven pituitary carcinomas using immunocytochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
104
5
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 45 publications
17
104
5
2
Order By: Relevance
“…18 The role of COX-2 in promoting metastasis relates to its activity as a tumor promoter by its stimulation of angiogenesis and metalloproteinase activity. 19,20 Although pituitary carcinomas are more vascularized than adenomas, 25 the occurrence of cerebrospinal metastases in these rare tumors suggests that hematogenous spread is not the exclusive domain of metastasis. This may explain partially a recent report that concluded that metalloproteinase activity in pituitary tumors does not correlate with metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 The role of COX-2 in promoting metastasis relates to its activity as a tumor promoter by its stimulation of angiogenesis and metalloproteinase activity. 19,20 Although pituitary carcinomas are more vascularized than adenomas, 25 the occurrence of cerebrospinal metastases in these rare tumors suggests that hematogenous spread is not the exclusive domain of metastasis. This may explain partially a recent report that concluded that metalloproteinase activity in pituitary tumors does not correlate with metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Details of immunohistochemistry, including the duration of exposure and control procedures for these three stains, as well as the morphometric quantification method have been described in previous publications. 25,26,32,33 Most tumors (n ϭ 119) were fixed in glutaraldehyde, routinely processed, embedded in Epon-Araldite, and studied by transmission electron microscopy.…”
Section: Morphologic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17]36,37 In addition, the assessment of MVD in a primary tumor ultimately may prove to be a significant and independent prognostic parameter related to tumor recurrence, metastasis, and overall patient survival. [37][38][39][40][41][42] The prognostic significance of angiogenesis has been confirmed in different types of brain tumors, e.g., diffuse astrocytomas of varying grade. In all of these tumors, angiogenesis correlates with tumor behavior and altered function of the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Both reactions were quanti ed in 29 randomly selected elds (6.7 mm 2 ) and expressed as the percentage of tumor area occupied by CD34-positive vessels (Vidal et al, 2001a), and the percentage of tumor tissue occupied by nucleated VEGFimmunoreactive cells. The latter was calculated as previously described (Vidal et al, 2001). In situ hybridization for VEGFR2 mRNA was carried out as previously described (Qian et al, 2001) using an oligonucleotide probe complementary to regions 309-318 of human mVEGFR2.…”
Section: Angiogenesis Studiesmentioning
confidence: 99%